2011
DOI: 10.1021/bi101892z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DypB from Rhodococcus jostii RHA1 as a Lignin Peroxidase

Abstract: Rhodococcus jostii RHA1, a polychlorinated biphenyl-degrading soil bacterium whose genome has been sequenced, shows lignin degrading activity in two recently developed spectrophotometric assays. Bioinformatic analysis reveals two unannotated peroxidase genes present in the genome of R. jostii RHA1 with sequence similarity to open reading frames in other lignin-degrading microbes. They are members of the Dyp peroxidase family and were annotated as DypA and DypB, on the basis of bioinformatic analysis. Assay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
372
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(392 citation statements)
references
References 40 publications
13
372
0
Order By: Relevance
“…Accordingly, purified proteins were reconstituted with heme as previously described (2). The spectra of the D153A, N246A, and D153A/N246A variants were remarkably similar to that of the WT, with a Soret band at 404 nm and the charge transfer band 1 at 632 nm (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Accordingly, purified proteins were reconstituted with heme as previously described (2). The spectra of the D153A, N246A, and D153A/N246A variants were remarkably similar to that of the WT, with a Soret band at 404 nm and the charge transfer band 1 at 632 nm (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Recombinant DypB and Variants-Wild-type DypB (WT) was heterologously produced in E. coli BL21(DE3) using pETDYPB1 as described elsewhere (2). The variants were constructed using oligonucleotide-directed mutagenesis as described in the supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…B-type DyPs also show activity towards anthraquinone dyes and phenolic substrates, but Rhodococcus jostii DypB has been shown to oxidise a lignin -aryl ether model compound and Mn 2+ , and in the presence of Mn 2+ shows oxidation activity towards polymeric lignin [9]. C-type DyPs such as DyP2 from Amycolatopsis sp.…”
Section: Introductionmentioning
confidence: 99%
“…1A). DyP-type peroxidases are a novel family of fungal and bacterial heme-dependent peroxidases that can oxidize lignin and anthraquinone dyes in the presence of H 2 O 2 (9,10). However, the Escherichia coli DyP ortholog, Ec-YfeX, was proposed to possess deferrochelatase activity, where Ec-YfeX can catalyze the extraction of iron from heme without cleavage of the tetrapyrrole ring (11), although in a parallel study, Ec-YfeX was demonstrated to be a heme-dependent peroxidase with no detectable deferrochelatase activity (12).…”
mentioning
confidence: 99%